Preparation and Characterization of Febuxostat as Nanosuspension - Zahraa Salim Alwan; Nawal Ayash Rajab (Iraqi Journal of Pharmaceutical Sciences, 2025)
Febuxostat (FEB) is a potent, non-purine-selective inhibitor of xanthine oxidoreductase used to manage gout. Gout is a type of arthritis that occurs due to the accumulation of uric acid crystals in the joints, leading to inflammation and pain. According to the Biopharmaceutical Classification System (BCS), FEB was classified under class II drugs. The low dissolution rate of the drug determines its bioavailability at approximately 49%. Drug nanosizing, such as Nanosuspensions (NS), represents an exciting and potentially beneficial method to improve the bioavailability of hydrophobic drugs. This study aimed to prepare and characterize FEB NS to increase the dissolution rate, which can enhance its oral bioavailability. Using solvent/anti-solvent precipitation, 40mg of FEB was dissolved in ethanol and dropped into an antisolvent system containing distilled water, water-soluble stabilizers (L-arginine and Soluplus), and co-stabilizers (Poloxamer 407 and Tween 80) in different ratios. FEB NS formulas were characterized based on particle size (P.S), polydispersity index (PDI), and in vitro dissolution studies. The optimized formula (F7) was further characterized using X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy. PDI of 0.13 ± 0.01 and P.S of 62.46 nm ± 0.015 was observed with the selected formula, which contained FEB, Soluplus, and tween 80 in a ratio of (1:4:0.5). A significant increase in drug release was observed at 60 minutes over ordinary FEB suspension. Consequently, Soluplus was the best stabilizer, and the solvent-antisolvent method to prepare FEB NS was successful. Therefore, NS is a valuable approach to improving the solubility of FEB, a BCS Class II drug.